51.1k views
5 votes
Solve the qn in attachment .​

Solve the qn in attachment .​-example-1

2 Answers

4 votes

Answer:


( (3)/(x - 1) - 4)/(2 - (2)/(x - 1) ) \\ = ( (3 - 4(x - 1))/(x - 1) )/( (2(x - 1))/(x - 1) ) \\ = (3 - 4x + 4)/(2x - 2) \\ ( - 4x + 7)/(2(x - 1)) \\ option \: b \: is \: your \: answer \\ thank \: you

User Osman Mamun
by
5.0k points
3 votes

Answer:


\implies ( -4x+7)/(2(x-2) )

Explanation:

The given expression to us is ,


\implies (( 3)/(x-1) -4 )/( 2 -(2)/(x-1))

Now take the LCM as ( x - 1 ) and Simplify , we have ,


\implies (( 3 -4(x-1) )/(x-1) )/( (2-2(2x-1))/(x-1))

Simplifying further , we get ,


\implies ( -4x+7)/(2(x-2) )

Hence the second option is correct.

User Adalcar
by
4.6k points